Recommendations for core critical care ultrasound competencies as a part of specialist training in multidisciplinary intensive care: a framework proposed by the European Society of Intensive Care Medicine (ESICM) - Wong, Adrian; Galarza, Laura; Forni, Lui; De Backer, Daniel; Slama, Michael; Cholley, Bernard; Mayo, Paul; McLean, Anthony; Vieillard-Baron, Antoine; Lichtenstein, Daniel; Volpicelli, Giovanni; Arntfield, Robert; et al. (Critical care (London, England), 2020)
UNLABELLED: Critical care ultrasound (CCUS) is an essential component of intensive care practice. Although existing international guidelines have focused on training principles and determining competency in CCUS, few countries have managed to operationalize this guidance into an accessible, well-structured programme for clinicians training in multidisciplinary intensive care. We seek to update and reaffirm appropriate CCUS scope so that it may be integrated into the international Competency-based Training in Intensive Care Medicine. The resulting recommendations offer the most contemporary and evolved set of core CCUS competencies for an intensive care clinician yet described. Importantly, we discuss the rationale for inclusion but also exclusion of competencies listed. BACKGROUND/AIM: Critical care ultrasound (CCUS) is an essential component of intensive care practice. The purpose of this consensus document is to determine those CCUS competencies that should be a mandatory part of training in multidisciplinary intensive care. METHODS: A three-round Delphi method followed by face-to-face meeting among 32 CCUS experts nominated by the European Society of Intensive Care Medicine. Agreement of at least 90% of experts was needed in order to enlist a competency as mandatory. RESULTS: The final list of competencies includes 15 echocardiographic, 5 thoracic, 4 abdominal, deep vein thrombosis diagnosis and central venous access aid. CONCLUSION: The resulting recommendations offer the most contemporary and evolved set of core CCUS competencies for an intensive care clinician yet described.
Keywords: Education, Medical, Graduate; Intensive Care Units; Critical Care; lidé; Humans; Delphi Technique; péče o pacienty v kritickém stavu; Ultrasonography; průzkumy a dotazníky; Competencies; Core critical care ultrasound; delfská metoda; ultrasonografie; Clinical Competence; jednotky intenzivní péče; Education, Medical, Continuing; kontinuální vzdělávání lékařů; Specialist training; klinické kompetence; Education in intensive care; Surveys and Questionnaires; studium lékařství specializační postgraduální